МЕТОДИЧЕСКОЕ ОПИСАНИЕ «ГЕЙМФИКАЦИЯ» И «ДИДАКТИЧЕСКИХ ПРОЦЕССОВ» (Scientific journal of the Fergana State University, 2023)
The article discusses information on improving the efficiency of the educational process in teaching information technology in education. It is theoretically analyzed that gamification technology is effective in the formation and development of personal professional skills. When teaching fanlap with the help of gamification in the educational process, the issues of developing the cognitive activity of students in order to form professional skills are presented.